PENGARUH MEDIA EDITING VIDEO BERBENTUK TUTORIAL PEMBELAJARAN TERHADAP KREATIVITAS BELAJAR SISWA KELAS XI PADA MATA PELAJARAN PRAKARYA - Mar'aen, Mar'aen; Mujiburrahman, Mujiburrahman (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2020)
The purpose of this study was to determined The Effect of Video Editing Tutorials towards students’ Creativity Class XI at MA Darul Qur'an Wal Hadits Sekotong Tengah in Academic Year 2018/2019. This study used samples from class XI at MA Darul Qur'an Wal Hadits Telaga Lebur Sekotong Tengah, West Lombok. This research was quantitative research to determined The Effect of Video Editing Tutorials towards students’ Creativity Class XI at MA Darul Qur'an Wal Hadits Sekotong Tengah. The method used in this study was questionnaire as the main method, observation and documentation as a complementary method. Data analysis used statistical analysis chi square formula. The analysis was results obtained value = 15,943 while the chi square db (C-1) x (R-1) = (5-1) x (2-1) = 4 with a significance level of 5% = 9,488 thus that the value Chi square analysis was greater than the chi square table (15,943> 9,488). This means that the null hypothesis was rejected and the alternative hypothesis was accepted is: there was The Effect of Video Editing Tutorials towards students’ Creativity Class XI at MA Darul Qur'an Wal Hadits Sekotong Tengah in Academic Year 2018/2019. so it can be concluded that the results of this study was "significant".